Movement posture and injury pattern of pelvis-lumbar spine of seated human impacted by the vertical high loads: a finite element analysis. Issue 7 (19th May 2023) - Jiang, Yongbo; Xiong, Xun; Chen, Zihao; Li, Ying
Abstract: The injury conditions of the sitting position occupant inside the military equipment are highly related to the vertical impact environments. In this study, a detailed three-dimensional finite element (FE) model of pelvis-lumbar spine of seated human with nonlinear material property and strain failure criterion was developed and validated. A series of sinusoidal accelerations with a constant peak speed of 8 m/s and frequencies ranging from 10 Hz to 90 Hz were loaded on the FE model to investigate the injury conditions under different high loading rates. The results indicated that the injury patterns mainly include wedge fracture of the junction between lumbar spine and pelvis, and comminuted fracture of ischial tuberosity. The bending moment caused by the large angle deflection of pelvis under 10 Hz case (low rate) and the acting force caused by the excessive curvature of lumbar spine under 30 Hz–70 Hz cases (medium and high rate) cause the junction wedge fractured, while the high impact force under 30 Hz–50 Hz cases (medium rate) leads to comminuted fracture of the ischial tuberosity. The associated mechanism that the shorter the time interval between the peak of seat loading speed and the peak of hip muscle compression, the more serious dynamic responses of pelvis-lumbar spine is revealed for the first time.